Interpretation of the Recent Seismic Activity of the Intraplate Zone in the Iberian Peninsula, Guadalajara, Spain - Cotilla-Rodríguez, Mario Octavio (2018)
The occurrence of 130 earthquakes (2007-2017) in the intraplate zone of the Iberian Peninsula validates the morphotectonic regionalization of the province of Guadalajara in 2004. These earthquakes were located in three blocks (BG6, BG7, and BG8) of the eastern-most mesoblock (6.3) included in the intermediate macroblock.